Hybridising the cultural identity of Mulan from a Chinese ballad to American films - Zhao, Meijuan; Ang, Lay Hoon; Haw, Florence Ching Toh (Brill Academic Publishers, 2022)
Hybridisation refers to the fusion of diverse cultural elements which generates new cultural forms that are distinct yet interconnected with one another. Previous studies affirmed that hybridisation has become part of an ongoing trend in transnational culture, emerging from a Third Space where diverse cultural elements enmesh. This study aims to explore how Mulan's cultural identity is hybridised when the folklore flows from China to America, becoming entangled within a conflict of Chinese-Western transcultural clashes. Using Jameson's cultural identity model, the paper analyses Mulan's cultural identity in three texts which are the original The Ballad of Mulan, Disney's animated movie Mulan (1998) and its subsequent life-action installment Mulan (2020). Components measuring the protagonist's cultural identity comprising vocation, class, geography, philosophy, language, biological traits with cultural aspects are compared. The findings show that the movies have particularly hybridise the protagonist's cultural identity from the aspects of geography, philosophy, and language. This results in a hybrid cultural identity with transnational markers in Mulan. The significance of the research thus lies in its contribution towards highlighting how Chinese figures are increasingly hybridised by Western influences as the Chinese culture continues to transcend transnational borders.